Mengembangkan Keterampilan Berbahasa Melalui Program Kampus Mengajar Mitra USU Di SDN 060807 Kota Medan - Chintya Khasanah Sianturi; Malida Putri (Universitas Maritim AMNI Semarang, 2023)
The USU Partner Teaching Campus is one of the Merdeka Belajar - Kampus Merdeka (MBKM) programs applied by the University of Sumatra in collaboration with the Medan City Education Office. The USU Partner Teaching Campus is paired with Field Work Practice (PKL) 1 of the Social Welfare Study Program, Faculty of Social and Political Sciences, University of North Sumatra. The USU Partner Teaching Campus as well as PKL 1 was carried out by practitioners at UPT SD Negeri 060807 Medan City which is located at Jl. Halat No.48, Pasar Merah Barat, Medan City. Practitioners carry out the program Developing Student Language Skills to grade V (five) students. Language skills consist of 4 aspects, namely: listening, speaking, reading and writing. In running the program, practitioners relate to using the Social Work intervention method in general stages which consists of engagement and intake contract, assessment, planning, intervention, termination and evaluation. To see the success of the program, practitioners make several outputs that must be achieved and give post tests to students. The results of the post test showed that the language skills of grade V (five) students of SDN 060807 Medan City improved compared to before.